2009
DOI: 10.18579/jpcrkc/2009/8/1/79523
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Snail Mucin on the Ulcer Healing Rate of Clarithromycin

Abstract: The effect of mucin on the ulcer-healing rate of clarithromycin has been investigated. The snail mucin extract was obtained from the giant African snail, Achatina achatina (Family Arionidae). The mucin was precipitated with acetone, collected and air-dried. Ulcers were induced with indomethacin in rats. The ulcer-healing rate was determined for clarithromycin alone, mucin alone and the combination of both. The control group did not receive any of the drugs. The results showed that the healing rate of clarithro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…For deep partial thickness facial burns, Helix aspersa extract had lower times for eschar detachment and burn surface epithelization in comparison to moist exposure burn ointment 40 . Similar to burns, gastric ulcers were also healed at a faster rate when clarithromycin was combined with mucin from the giant African snail 41 . In mice with experimentally induced testicular damage and intestinal inflammation via carbon tetrachloride (CCl 4 ), Eremina desertorum snail mucin provided notable antioxidant and anti‐inflammatory effects as evidenced by histopathology 42 .…”
Section: Functions Of Snail Mucin In Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…For deep partial thickness facial burns, Helix aspersa extract had lower times for eschar detachment and burn surface epithelization in comparison to moist exposure burn ointment 40 . Similar to burns, gastric ulcers were also healed at a faster rate when clarithromycin was combined with mucin from the giant African snail 41 . In mice with experimentally induced testicular damage and intestinal inflammation via carbon tetrachloride (CCl 4 ), Eremina desertorum snail mucin provided notable antioxidant and anti‐inflammatory effects as evidenced by histopathology 42 .…”
Section: Functions Of Snail Mucin In Medicinementioning
confidence: 99%
“…40 Similar to burns, gastric ulcers were also healed at a faster rate when clarithromycin was combined with mucin from the giant African snail. 41 In mice with experimentally induced testicular damage and intestinal inflammation via carbon tetrachloride (CCl 4 ), Eremina desertorum snail mucin provided notable antioxidant and anti-inflammatory effects as evidenced by histopathology. 42 Airway epithelium has also seen benefit from snail mucin in which helcidine extracted from Helix pomatia was seen to relax the trachea via release of prostaglandin E2, suggesting a potential broncho-relaxant and antitussive agent.…”
Section: Fun C Ti On S Of S Nail Mucin In Medicinementioning
confidence: 99%
“…The regenerative capacity of snail mucus against their own shell and skin injuries attracted human attention, and it has been traditionally used therapeutically against gastrointestinal ulcers since ancient Greece [ 6 , 7 ]. Nowadays, studies have demonstrated the protective effect of mucus from the giant African snail in different models of gastric ulcers: induced by indomethacin, histamine, and prolonged exposure of the experimental mice to cold [ 8 , 9 ]. The results show a pronounced beneficial effect, likely due to the cytoprotective and antispasmodic action of the mucus.…”
Section: Introductionmentioning
confidence: 99%
“…Many companies have turned to natural products to counteract these side effect, and Mucin have been shown to treat peptic ulcers, a side effects caused by NSAIDs ( Drina, 2017 ). A combination of the antibiotic, clarithromycin, and A. fulica mucin has shown positive results in treatment of peptic ulcer disease ( Mu et al, 2008 ; Kabakambira et al, 2018 ). In addition to anti-ulcer properties, the healing rate of ulcers increased with concentration of mucin and was faster than clarithromycin alone.…”
Section: Introductionmentioning
confidence: 99%